A complementary perspective on legitimation in regional development: The crisis of acceptance of liquefied natural gas (LNG) on the touristic island of Rügen; Eine komplementäre Perspektive auf Legitimation in der Regionalentwicklung: Die Akzeptanzkrise von Flüssigerdgas (LNG) auf der Touristen-Insel Rügen - Ihar Buika; Daniel Schiller (Raumforschung und Raumordnung / Spatial Research and Planning, 2025)
As the substance of public interest in spatial planning and development remains permanently challenged, the relationship between legitimacy and acceptance is constantly in the focus of discussion. After the wave of interest in participation-intensive communicative legitimation approaches from the 1970s, a still new generation of agonistic approaches has been intensively discussed since the 2000s, raising expectations of a more efficient resolution of conflicts which continue to pose a risk of disturbing or preventing deliberative negotiation. Although such approaches are participation-oriented, too, there are nevertheless concerns that these expectations could remain unfulfilled like those regarding the communicative approach nowadays are. Against this background, our qualitative study, based on 20 semi-structured interviews, is intended to enrich discussion about the complementary perspective on legitimation by clarifying aspects that condition the composition of rational, communicative and agonistic legitimation approaches in particular development projects. The protest against the liquefied natural gas terminal on the island Rügen demonstrates that strong recourse to the rational legitimation approach has restricted participation and thus overshadowed communicative and agonistic demands for broader local participation and led to a severe crisis of acceptance. We argue that it is essential in terms of acceptance-fostering to counter complex issues with equally complex solutions. Moreover, effective and accepted planning and development policy depends on a spatially and temporally sensible, pragmatic composition of legitimation approaches. – – So wie das Wesen des öffentlichen Interesses in der Raumplanung und Raumentwicklung permanent infrage gestellt wird, steht das Verhältnis von Legitimität und Akzeptanz ständig im Mittelpunkt der Diskussion. Nach der Welle des Interesses an partizipationsintensiven kommunikativen Legitimationsansätzen seit den 1970er-Jahren, wird seit den 2000er-Jahren eine neue Generation von agonistischen Ansätzen intensiv diskutiert und weckt Erwartungen an eine effizientere Lösung von Konflikten, die nach wie vor die Gefahr bergen, deliberative Diskussionen zu stören oder zu verhindern. Auch wenn solche Ansätze ebenfalls partizipationsorientiert sind, bestehen jedoch Bedenken, dass diese Erwartungen ebenso unerfüllt bleiben könnten wie die an den kommunikativen Ansatz. Vor diesem Hintergrund soll unsere, auf 20 halbstrukturierte Interviews gestützte qualitative Studie die Diskussion über die komplementäre Perspektive auf Legitimation bereichern, indem sie Aspekte klärt, die die Zusammensetzung von rationalen, kommunikativen und agonistischen Legitimationsansätzen in einzelnen Entwicklungsprojekten bedingen. Der Protest gegen das Flüssigerdgas-(LNG)Terminal auf der Insel Rügen zeigt, dass der starke Rückgriff auf den partizipationseinschränkenden rationalen Legitimationsansatz die kommunikativen und agonistischen Ansprüche und Bedarfe für mehr Partizipation vor Ort überschattet und zu einer schweren Akzeptanzkrise geführt hat. Wir argumentieren, dass es im Sinne der Akzeptanzförderung entscheidend ist, komplexe Herausforderungen mit ebenso komplexen Lösungen anzugehen. Eine effektive und akzeptierte Raumplanungs- und -entwicklungspolitik hängt von einer räumlich und zeitlich sensiblen, pragmatischen Zusammensetzung der Legitimationsansätze ab.
Keywords: 710; Legitimacy; Acceptance; Liquefied; natural gas (LNG); Complementary perspective; Protest; Legitimität; Akzeptanz; Flüssigerdgas (LNG); Komplementäre Perspektive